The Summary of the Scale and the Treatment Measures in Oilfield - Liu, Jianghong; Zhang, Yan; Ren, Jingwei; Wang, Huaiyuan; Zhang, Tie; Lu, Yan (Recent Innovations in Chemical Engineering, 2015)
The normal production of oil fields was seriously affected by the mineral scale formation, especially calcium deposition. This paper focused on the types, mechanisms and influencing factors of common scales oilfield scaling, especially carbonate scale and sulfate scale. Besides, some prediction models which were widely practiced in the oilfield to determine the scaling tendency of oilfield brine were described. The development and scale inhibition mechanisms of scale inhibitors which were used in oilfield were introduced and the scale removal and inhibition technology were reviewed. Furthermore, some patents of scale inhibitors and removal technology were commented.
Keywords: prediction models